Data Science Approach for Rapid COVID-19 Case Rate Study of Important Climatic Regions in Correlation with Temperature and Humidity Variations of INDIA (International Journal of Innovative Research in Computer Science & Technology, 2021)
The early pandemic wave came after the  imposition of Lockdown by Indian Government. Although  it wasn’t clear if factors like temperature and humidity have  any correlation with the increase of cases in the Locked  regions of the state, as studies were on going in virology  and biotechnological field for that matter. We took public  health vision for the study, by considering five important  climatic regions of the nation with different temperature  and humidity in a scientific attempt to provide correlation  between these factors and rising COVID 19 case counts in  India. Crowd source data was used for the analysis in this  study. Initial database of confirmed case counts of COVID  19, humidity, maximum and minimum temperature of five  important climatic regions was created. The data collected  was removed of redundancies and mean average figures  were calculated, to perform correlation analysis on the  database using SPYDER (The Scientific Python  Development Interface). Statistical approaches such as  Pearson correlation coefficient and linear regression curve  graphical representation was used for the analysis. The  analysis significantly presented positive correlation  between confirm case count increase and climatic factors  (humidity and temperature) in five different climatic  regions of India for the period of four lockdowns. The  analysis proved the region with greater humidity was  suffering on a great frequency with respect to less humid  region. Average temperature was nearly equal for every  climatic region, nevertheless the analysis presented with  figures signifying nearly nil or low positive correlation  between confirmed case count ratio and climatic regions  with high or low mean average temperature. It was evident  that climatic factors had an impact on the transmission and  sustaining capability of COVID 19. The analysis of  different climatic regions that also during the period of  Lockdown is essential to health care sector, government  and policy makers while making new policy decisions and  taking new measures for prevention of spread of COVID 19  pandemic and any future pandemic scenarios of the level.
Keywords: COVID-19; Climatic factors; correlation; confirmed cases count; India